The Safety and Immunogenicity of a Quadrivalent Influenza Subunit Vaccine in Healthy Children Aged 6–35 Months: A Randomized, Blinded and Positive-Controlled Phase III Clinical Trial - Lili Huang; Guangfu Li; Yuhui Zhang; Xue Zhao; Kai Wang; Chunyu Jia; Wei Zhang; Jiebing Tan; Xiaofen Chen; Qin Li; Hongyan Jiang; Rui An; et al. (Vaccines)
Background: Influenza is a serious contagious disease caused by influenza virus. It is particularly dangerous for children, potentially leading to severe and even fatal complications. The aim of this study was to evaluate the safety and immunogenicity of two candidate quadrivalent influenza subunit vaccines in children aged 6–35 months. Methods: The subjects were randomly divided into three groups at a 1:1:1 ratio and received the corresponding vaccines: QIV-Sub-HD (Quadrivalent Influenza Subunit Vaccine, High Dose), QIV-Sub-LD (Quadrivalent Influenza Subunit Vaccine, Low Dose) and QIV-Split-LD (Quadrivalent Influenza Split-Virion Vaccine, Low Dose). Adverse events were recorded at 30 min, 0–7 days and 8–28 and 30 days after each dose of immunization. Serious adverse events (SAEs) were collected and reported within 6 months after the full vaccination. Blood samples were collected before the first dose and on 28 days, 3 months and 6 months after full vaccination for antibody detection to evaluate the immunogenicity and duration of immune responses. Results: The results showed that the relative and absolute criteria met the goals set by the clinical trial protocol, indicating that both vaccines are immunogenic. From the first dose to 30 days after full vaccination, the total incidence of adverse reactions in the QIV-Sub-HD, QIV-Sub-LD and QIV-Split-LD groups was 29.64%, 33.33% and 29.64%, respectively. The main symptoms were fever, cough, diarrhea and vomiting. No new safety concerns were identified. Conclusions: The quadrivalent influenza subunit vaccines candidate, manufactured by Ab&B Bio-tech Co., Ltd. JS., are safe and immunogenic in children aged 6–35 months.